THE TEACHER'S ROLE AS A PEDAGOGICAL COORDINATOR AND ITS OBSTACLES - Ramos Pereira de Souza, Diego; Alexandre Agreli de Lira Miranda, Ricardo; da Silva Costa, Jucelino; Marcia de Mendonça Oliveira, Girlaine; Aparecida Santos da Silva, Maria; Wilker da Silva, José; de Gouvêa Caldas, Glauco; Maria do Nascimento Domingos, Ramires; Maria Alves, Ivanilda; Bruna da Silva, Maria; de Melo Silva, Inaldevania (Revista Gênero e Interdisciplinaridade, 2025)
Since society is changeable, fluid and tangible, social reality must be constantly observed. Thus, if we consider that the school is a space of socialization, a space where one of the first contacts and interactions of the child in society occurs. It is within this framework that the coordination becomes practical for solving problems and seeking results in the teaching-learning process. The article aims to discuss the difficulties faced by the pedagogical coordinator. And in this line of research it was in the interest of the researcher to discuss the social function of the school, the attributions of the pedagogical coordinator and its consequent need for adaptation. The methodology adopted was the bibliographic review of the digital material of the academic databases.